Hints and tips in revision hip surgery. Issue 1 (February 2018) - Ward, Jonathan; Clark, Rhys; Morris, Guy; Jeys, Lee
Abstract: Revision total hip arthroplasty has excellent results but is challenging surgery. A myriad of considerations and complications face the surgeon but careful planning and careful execution of that plan can reduce the likelihood of failure. This review article attempts to give practical advice on managing preoperative planning, intraoperative considerations and postoperative complications for the reader.